2001
DOI: 10.1046/j.1365-2133.2001.04143.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene polymorphisms in psoriasis

Abstract: Psoriasis is not determined by a genotype consistent with high production of Th1 cytokines or low production of Th2 cytokines. Thus, the Th1 cytokine profile found in psoriatic plaques is most likely a consequence of local factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
65
3
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 39 publications
6
65
3
4
Order By: Relevance
“…Chronic AD skin lesions have significantly fewer Th2 cytokine-, but greater numbers of Th1 cytokine-expressing cells, than in acute AD [8] . Psoriasis patients exhibit a Th1 bias in the lesion skin and in the peripheral blood, and are thought to develop Th1 cytokine networks [13] . Indeed, tacrolimus hydrate (tacrolimus), a potent immunosuppressant that is currently used topically in the treatment of AD and psoriasis, suppressed the cutaneous inflammation in this model.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic AD skin lesions have significantly fewer Th2 cytokine-, but greater numbers of Th1 cytokine-expressing cells, than in acute AD [8] . Psoriasis patients exhibit a Th1 bias in the lesion skin and in the peripheral blood, and are thought to develop Th1 cytokine networks [13] . Indeed, tacrolimus hydrate (tacrolimus), a potent immunosuppressant that is currently used topically in the treatment of AD and psoriasis, suppressed the cutaneous inflammation in this model.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] A number of studies have been presented providing evidence for associations between these IL-10 promoter variants and infectious or autoimmune diseases, including meningococcal infection, fatal septicemia, systemic lupus erythematodes, reactive arthritis, psoriasis, Sjogreń s syndrome, and multiple sclerosis. 10,12,[16][17][18][19][20] So far, it has not been studied, however, whether IL-10 promoter variants influence lymphocyte proliferation upon antigen stimulation, a major regulatory function attributed to IL-10.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Up to now only few studies have showed an association between IL-10 promoter SNPs and the susceptibility to psoriasis. 14,15 In the light of the above findings, the aim of this study was to determine the distribution of the IL-10 5 0 flanking region haplotypes in psoriasis patients and in healthy controls, and to investigate whether polymorphisms at IL-10 promoter region influence susceptibility to and/or severity in this chronic skin disease.…”
mentioning
confidence: 99%